The Cost of Services Provided in the Physiotherapy Department of Shafa Yahyaian Hospital - Azimeh Golmohammad; Farbod EbadifardAzar; Ali Abutorabi (Kerman University of Medical Sciences, 2020)
The Cost of Services Provided in the Physiotherapy Department of Shafa Yahyaian Hospital   Golmohammad Azimeh1, Ebadi Fard Azar Farbod2*, Abutorabi Ali3   1. M.Sc. Student in Health Economics, Department of Health Economics, Faculty of Health Management and Information Sciences, Iran University of Medical Sciences, Tehran, Iran 2. Professor, Department of Health Promotion and Education, Faculty of Public Health, Iran University of Medical Sciences, Tehran, Iran 3. Assistant Professor, Department of Health Economics, Faculty of Health Management and Information Sciences, Iran University of Medical Sciences, Tehran, Iran *Corresponding Author: Farbod Ebadi Fard Azar Address: Iran University of Medical Sciences, Shahid Hemmat Highway, Tehran, Iran Tel: 00982186702108                                               Email: Ebadifardazar.f@iums.ac.ir                     Abstract: Background & Objectives: Our country is facing increasing costs of treatment and funding shortages. The reason for this crisis is the increase in the cost of medicine, medical equipment, and skilled manpower. The physiotherapy unit is one of the cost centers and accounts for a large share of hospital costs. Managers and policymakers must pay special attention to cost centers in order to make decisions about reducing costs and increasing efficiency. Methods: The present study was a retrospective economic evaluation that was conducted in 2018 based on activity-based costing. The data were collected by referring to the Physiotherapy, Employment, Finance, Medical Equipment and Warehouse Units. To calculate the cost of physiotherapy services, the salaries of staff working in the units as well as the cost of the consumables, depreciation of buildings and equipment and energy were estimated in detail. Results: The total annual costs of the physiotherapy unit amounted to 8415722668 rials and the annual loss of the mentioned unit amounted to 1287632108 rials. The highest costs were for physiotherapists, accounting for 82% of the total costs, overhead costs, accounting for 8.1%, and depreciation of medical equipment. Conclusion: According to the losses imposed on physiotherapy unit, one of the suggested options is unit outsourcing. Running evening shifts, paying fee-for-service due to high personnel costs, and hiring a non-faculty technical manager with a lower salary can be effective in reducing the average unit cost.   Keywords: Activity-Based Costing, Tariff, Physiotherapy, Teaching Hospital, Overhead Cost   Citation: Golmohammad A, Ebadi Fard Azar F, Abutorabi A. The Cost of Services Provided in the Physiotherapy Department of Shafa Yahyaian Hospital. Journal of Health Based Research 2020; 5(3): 355-367. [In Persian]